Analysis of zwitterionic membrane fouling mechanism caused by HPAM in the presence of electrolytes. Issue 27 (4th May 2021) - Jiang, Qin; Liu, Zi-Yu; Guo, Wei; Su, Zengping; Ma, Wangjing; Zhang, Lu; Zhao, Sui
Abstract : The foulant HPAM and electrolyte CaCl2 are used to investigate the fouling mechanism of zwitterionic membrane dealing with HPAM in saline wastewater. Abstract : Membrane fouling has always been a tough issue that is urgent to solve. Electrolytes which are prevalent in wastewater have a major influence on membrane fouling. Therefore, it is of great significance to understand the role and fouling mechanism of electrolytes in the membrane fouling process. In this work, the zwitterionic membrane is used to process hydrolyzed poly(acrylamide) (HPAM) with the addition of electrolytes (CaCl2, NaCl). Meanwhile, the effect of different electrolytes on the zwitterionic membrane fouling process by hydrolyzed poly(acrylamide) (HPAM) is systematically investigated. It was found that the flux recovery ratio (FRR) of the zwitterionic membrane is nearly 100% after treating HPAM with the addition of electrolytes. Therefore, molecular dynamics (MD) simulations were applied to illustrate the impact of electrolytes on the change of foulant structures and confirm the consequent effect of electrolytes on membrane fouling. According to the experiment and MD simulation results, it is found that the positive ion layer which exists between the HPAM and zwitterionic surface results in the excellent fouling resistance performance of the zwitterionic membrane. The zwitterionic membrane fouling mechanism is analyzed, which is helpful to the understanding of zwitterionic membrane fouling in high salinity wastewater.